2013
DOI: 10.3844/ajavsp.2013.104.111
|View full text |Cite
|
Sign up to set email alerts
|

CLINICAL AND REPRODUCTIVE PATHOLOGICAL CHANGES ASSOCIATED WITH <i>BRUCELLA MELITENSIS</i> AND ITS LIPOPOLYSACCHARIDES IN FEMALE MICE VIA ORAL INOCULATION

Abstract: Brucella melitensis (B. melitensis) are Gram-negative, aerobic, facultative intracellular bacteria that cause brucellosis that usually leads to abortion in sheep and goats. Three groups of equal number of 24 healthy female mice were used as animal models. They were orally inoculated with 0.4 mL of phosphate Buffered Saline (PBSControl group), 0.4 mL of 10 9 cfu of B. melitensis and 0.4 mL of Lipopolysaccharides (LPS) extracted from 10 9 cfu of B. melitensis (both as treatment groups). Clinical signs exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…The pathological changes observed in the ovaries of Brucella-infected mice were in agreement with that previously reported by Abdullah et al (2013a). In a related study, Abdullah et al (2013bAbdullah et al ( , 2014 observed more severe degenerative and inflammatory changes in male and female reproductive organs of mice following intraperitoneal inoculation of B. melitensis and its lipopolysaccharide.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The pathological changes observed in the ovaries of Brucella-infected mice were in agreement with that previously reported by Abdullah et al (2013a). In a related study, Abdullah et al (2013bAbdullah et al ( , 2014 observed more severe degenerative and inflammatory changes in male and female reproductive organs of mice following intraperitoneal inoculation of B. melitensis and its lipopolysaccharide.…”
Section: Discussionsupporting
confidence: 90%
“…The pellet obtained after the extraction was washed with 1 ml 70 % ethanol and dried. Seventy microliters of 10-mM Tris-HCl buffer at pH 8.0 was added to the pallet and allowed to dissolve by boiling for 2 min (Abdullah et al 2013a(Abdullah et al , b, 2014.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In goats, brucellosis causes serious economic impact to goat farmers from abortions and stillbirths [2]. Infections by B. melitensis occur through mucous membrane of the nasopharynx as well as through ingestion of contaminated feed [3].…”
Section: Introductionmentioning
confidence: 99%